2014
DOI: 10.1128/jcm.00193-14
|View full text |Cite
|
Sign up to set email alerts
|

Routine Testing for Anaerobic Bacteria in Cerebrospinal Fluid Cultures Improves Recovery of Clinically Significant Pathogens

Abstract: cIn North America, the widespread use of vaccines targeting Haemophilus influenzae type b and Streptococcus pneumoniae have dramatically altered the epidemiology of bacterial meningitis, while the methodology for culturing cerebrospinal fluid (CSF) specimens has remained largely unchanged. The aims of this study were 2-fold: to document the current epidemiology of bacterial meningitis at a tertiary care medical center and to assess the clinical utility of routinely querying for anaerobes in CSF cultures. To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Prior antibiotic treatment is a common cause of falsely negative CSF Gram stain and culture, with up to 50% of patients having received antibiotics before CSF collection in some studies (21). Interlaboratory differences in the set up and processing of devicecollected CSF samples are another major cause of variable culture yield and performance across institutions (13,33,(42)(43)(44)(45). The recommendations regarding the need for CSF centrifugation prior to culture, anaerobic culture, anaerobic transport media, broth culture, duration of broth incubation, and the role, appropriateness, and procedure for CNS device tip cultures are frequently not explicit and differ between standard clinical microbiology references (44,45).…”
Section: Microbiologic Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior antibiotic treatment is a common cause of falsely negative CSF Gram stain and culture, with up to 50% of patients having received antibiotics before CSF collection in some studies (21). Interlaboratory differences in the set up and processing of devicecollected CSF samples are another major cause of variable culture yield and performance across institutions (13,33,(42)(43)(44)(45). The recommendations regarding the need for CSF centrifugation prior to culture, anaerobic culture, anaerobic transport media, broth culture, duration of broth incubation, and the role, appropriateness, and procedure for CNS device tip cultures are frequently not explicit and differ between standard clinical microbiology references (44,45).…”
Section: Microbiologic Testingmentioning
confidence: 99%
“…Several studies have reported an increase in the proportion of positive CSF cultures and clinically significant Propionibacterium spp. infections with the addition of anaerobic culture (solid media or broth) and prolonged incubation of broth media (10 to 14 days) (13,30,42,46). Calderaro et al observed a shorter time-to-positivity and a 79% increase in the detection of aerobic bacteria and yeast with an inoculation of 1 to 3 ml CSF into a Bactec Peds Plus/F blood culture bottle over that with conventional agar culture (43).…”
Section: Microbiologic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…P. acnes is a part of the normal flora of the skin and may be associated with biofilms . It is well recognized as a cause of CNS infections in patients with a CSF shunt or other foreign material present , but is often dismissed as a contaminant when it is recovered from CSF cultures from patients who do not have foreign material present.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial, mycobacterial, and fungal cultures were performed. The process used for CSF culture in the treating institution included centrifugation of the CSF specimen with inoculation of the sediment on sheep blood agar and chocolate agar (Remel, Lenexa, Kansas USA) incubated in 5% CO 2 for a minimum of 48 h, plus an anaerobic culture consisting of inoculation of sediment onto a pre‐reduced Brucella blood agar plate, which was incubated anaerobically for a total of 5 days . All cultures from his CSF were negative, as were PCR assays of CSF for herpes simplex virus (HSV), cytomegalovirus, human herpesvirus‐6, varicella zoster virus, and Toxoplasma gondii .…”
Section: Case Reportmentioning
confidence: 99%